Evaluation of Antiproliferative and Antioxidant effects of Dittrichia viscosa in Different Cell Lines - Dalkilic, Lütfiye Kadioglu; Dalkilic, Semih; Karaman, Fatih (My University, 2025)
Objective: Cancer is a complex group of diseases characterized by uncontrolled cell proliferation due to disorders at the physiological and molecular levels. In recent years, there has been an increased interest in anticancer compounds derived from environmentally friendly and low toxicity plant sources. In this context, it was aimed to evaluate the cytotoxic and antioxidant potential of Dittrichia viscosa, a plant belonging to the Asteraceae family and known for its anti-inflammatory, antimicrobial, anticancer and antidiabetic properties, on different cell lines. Materials and Methods: In this study, extracts were obtained from D. viscosa plant using methanol and hexane solvents. These extracts were prepared at eight different concentrations and applied on A549 (lung carcinoma), HEPG2 (liver carcinoma), MCF-7 and MDA-MB-231 (breast carcinoma) cell lines. Cell viability was analyzed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) test. In addition, the antioxidant activity of the hexane extract was determined by DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging method. Results: As a result of the analysis, it was observed that the highest cytotoxic effect was realized by 54% with hexane extract applied at a concentration of 100 ?g/ml in A549 cell line. In general, the hexane extract showed a stronger cytotoxic effect than the methanol extract. In DPPH assays, methanol and hexane extracts showed lower and more stable antioxidant effect and this effect was slightly higher in methanol extract than hexane. Conclusion: It was observed that especially the hexane extract of D. viscosa had a significant cytotoxic effect on some cancer cell lines. The high activity even at low concentrations in A549 and MDA-MB-231 cell lines indicates that this plant can be evaluated among potential anticancer agents. However, given the limited antioxidant activity, more extensive research on this effect of the plant is needed.
Keywords: Antioxidant; MTT assay; Cytotoxic activity; Dittrichia viscosa; Cell lines